An Evaluation of the Role of Religion and Politics in the Nation-Building Process in Nigeria Since Independence - Effiong Eke Nta; Kedei Iwara Esukpa; Franca Okey Ushie (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2026)
This study examines the role of religion and politics in Nigeria's nation-building process since independence in 1960. It reveals that both religious and political institutions have contributed significantly to Nigeria's nation-building narratives, with effects that have been both positive and negative on the desired outcome of national integration. The study clarifies key concepts, including religion, politics, and nation, while examining the process of nation-building and how religious and political institutions have influenced it in Nigeria. The research employed both primary and secondary data collection methods, utilising a multidisciplinary approach. The study posits that since religion and politics are often described as the "twin towers of identity," which can either provide a strong foundation or, if mismanaged, create deep structural cracks, ensuring they serve rather than subvert the nation-building process requires a shift from identity-based politics to issue-based governance.